Moving upstream: healthcare partnerships addressing social determinants of health through community wealth building - Geoffrey M. Gusoff; David Zuckerman; Bich Ha Pham; Gery W. Ryan (BMC, 2023)
Abstract Background Healthcare-based interventions addressing social needs such as food and housing generally fail to impact the upstream wealth and power inequities underlying those needs. However, a small number of US healthcare organizations have begun addressing these upstream inequities by partnering with community wealth building initiatives. These initiatives include community land trusts, resident-owned communities, and worker cooperatives, which provide local residents ownership and control over their housing and workplaces. While these partnerships represent a novel, upstream approach to the social determinants of health, no research has yet evaluated them. Methods To assess the current state and key aspects of healthcare-community wealth building partnerships, we conducted a multiple case study analysis using semi-structured interviews with thirty-eight key informants across ten partnerships identified through the Healthcare Anchor Network. To analyze the interviews, we used a two-stage coding process. First, we coded responses based on the phase of the intervention to which they corresponded: motivation, initiation, implementation, or evaluation. Then we assessed responses within each aspect for common themes and variation on salient topics. Results Partnerships were generally motivated by a combination of community needs, such as affordable housing and living wage jobs, and health system interests, such as workforce housing and supply chain resilience. Initiating projects required identifying external partners, educating leadership, and utilizing risk mitigation strategies to obtain health system buy-in. Implementation took various forms, with healthcare organizations providing financial capital in the form of grants and loans, social capital in the form of convening funders and other stakeholders, and/or capacity building support in the form of strategic planning or technical assistance resources. To evaluate projects, healthcare organizations used more process and community-level metrics rather than metrics based on individual health outcomes or returns on investment. Based on best practices from each partnership phase, we provide a roadmap for healthcare organizations to develop effective community wealth building partnerships. Conclusions Assessing healthcare partnerships with community wealth building organizations yields key strategies healthcare organizations can use to develop more effective partnerships to address the upstream causes of poor health.